ANALISIS KINERJA ORGANISASI KOMISI PENYIARAN INDONESIA PROVINSI JAWA TENGAH - Liansyah, Dwi Eki; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2018)
The era of globalization is now modern and it is characterized by the presence of increasingly advanced technology. Technology was created to facilitate the public in obtaining information. Information that can be obtained by the public via mass media such as television. With opennes of the pers, television broadcasts are free and need to be controlled so as not to violate the rules of P3SPS. The broadcaster in Central Java has a large number and wide range. The administrative recap provided by KPID of Central Java is not in accordance with the target. This study was designed to explain in more detail the performance of the Regional Indonesian Broadcasting Commission (KPID) of Central Java Province. This type of research is descriptive qualitative. Indicators that become performance appraisals include productivity, service quality, responsiveness, responsiveness, and accountability. The results of this research can be concluded that the performance of Central Java KPID in providing services to the community needs to be improved again. KPID Central Java has problems in the lack of supervision to the broadcaster, the realization of programs and activities also not in accordance with the time set in the regulation, broadcast permit requirements are complicated for the applicant, as well as regulations that have not updated its contents. The factors that inhibit the performance of Central Java KPID covering human resources and limited infrastructure facilities. Suggestions from researchers on the performance of KPID Central Java is the improvement of supervisory function by involving other public organizations, the addition of human resources and infrastructure facilities as needed, and the existing regulations need to be updated again its contents.